To convert exponential to radical expression and vice versa, we follow the pattern below:
![ab^{(x)/(n)}=a\sqrt[n]{b^x}^{}](https://img.qammunity.org/2023/formulas/mathematics/college/i5t5sdbm3580aqo5ftaftow2avh69a0kuh.png)
In the given term in the question, a = 5, b = x, n = 9, and x = 1. Let's plug these values into the radical form shown above.
The radical form of the given term is:
![5\sqrt[9]{x}](https://img.qammunity.org/2023/formulas/mathematics/college/neyaemz389kvgb85lc3gw7i34r8r8os2zn.png)